Commensal obligate anaerobic bacteria and health: production, storage, and delivery strategies - Andrade, José Carlos (2020)
In the last years several human commensals have emerged from the gut microbiota studies as potential probiotics or therapeutic agents. Strains of human gut inhabitants such as Akkermansia, Bacteroides, or Faecalibacterium have shown several interesting bioactivities and are thus currently being considered as food supplements or as live biotherapeutics, as is already the case with other human commensals such as bifidobacteria. The large-scale use of these bacteria will pose many challenges and drawbacks mainly because they are quite sensitive to oxygen and/or very difficult to cultivate. This review highlights the properties of some of the most promising human commensals bacteria and summarizes the most up-to-date knowledge on their potential health effects. A comprehensive outlook on the potential strategies currently employed and/or available to produce, stabilize, and deliver these microorganisms is also presented.